Unconventional Shrinkage of Hot Electron Distribution in Metal Directly Visualized by Ultrafast Imaging (Small Methods 2/2023). Issue 2 (17th February 2023) - Gao, Guoquan; Jiang, Lan; Xue, Bofeng; Yang, Fei; Wang, Ti; Wan, Yan; Zhu, Tong
Abstract : Inside Back Cover In article number 2201260, Zhu and co‐workers demonstrate an innovative strategy to directly track the evolution of hot electron temperature distribution with simultaneously high temporal and spatial resolution. An anomalous contraction of hot electron distribution unravels the competition between transport and cooling. This work enriches the tool kit of ultrafast techniques and provides guidance for rational design of micro/nanodevices.